Fundamentals of Management : text and Philippine Cases - Rodrigues, Rafael A. ([Manila, Philippines] : Diwata Publishing, Inc, 1993)
This second edition incorporates a number of important additions to the coverage of the first edition.
Part 1. Introduction Chapter 1. Managers and development -- Chapter 2. Origins and contemporary Management thought -- Chapter 3. The Firm and Its Environment. -- Chapter 4. Forms of Business Organizations in the Philippines. -- Part 2. Management Process -- Part 3. Business Management Functions .
Includes bibliographical references and index.
Keywords: MANAGEMENT -- PHILIPPINES